Effects of Polypropylene Waste Plastic as a Replacement to Coarse Aggregate on Mechanical Behavior of Self Compacting Concrete - Hamze, Fayad Mouhammad (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2018)
In recent years, the usage of recycled plastic aggregates as a replacement to aggregate has been taken into consideration to decrease the environmental effects of both concrete and waste plastics. Recycled plastic aggregate concrete, has come to be recognized as a distinctly promising technology capable of making useful contributions to resource performance in the production industry This thesis outlines an experimental study on the physical and mechanical properties of 0.45 w/b self-compacted concrete (SCC) manufactured using recycled polypropylene (PP) waste plastic as a replacement to natural coarse aggregates. It analyzes the effects of five different percentages (0, 5, 10, 15, 20 and 25%) of PP as a replacement to natural coarse aggregates on compressive strength, flexural strength, splitting tensile strength, workability, weight, ultrasonic pulse velocity and flexural toughness of SCC. It also studies the weight loss, pulse velocity, compressive, splitting and flexural strength changes, when specimens are exposed to two different temperatures as100℃ and 200℃. Experimental results show that; SCC mechanical and physical properties decreased with increased PP percentage up to 25%, because the mechanical and physical properties of SCC concretes, incorporated with PP are lower than those of concretes formed with natural aggregate. Polypropylene aggregates at high level (25%), has a positive effect on flexural toughness because they were used in small sizes, which could improve flexibility. Keywords: Self Compacted Concrete, Polypropylene waste plastic, lightweight aggregate, compressive strength, splitting tensile strength, flexural strength, workability, flexural toughness, Heat degradation.

ÖZ: Son yıllarda, atık plastiklerin parçalara ayrıştırılarak agrega yerine kullanılması konusu çok rağbet görmüş olup, hem atık plastiklerin hem de betonun çevreye olan zararlı etkileri azaltılmaya çalışılmaktadır. Atık plastik agrega ile üretilmiş betonlar, teknoloji tarafından kabul görmüş olup, araştırmacılar bu konuya katkı sağlamaya çalışılmaktadır. Bu deneysel çalışmada, s/ç = 0.45 olan, agrega yerine kısmen polipropolin (PP) atık plastik kullanılarak üretilmiş olan kendiliğinden yerleşen beton (KYB)’un fiziksel ve mekanik özelikleri araştırılmıştır. Agrega yerine betona katılmış olan atık PP parçaları betonun toplam hacminin % (0, 5, 10, 15, 20 and 25%)’i oranlarında betona katılmıştır. Bununla beraber, plastik agrega ile pasta arasındaki bağı arttırmak için karışımlara, çimento miktarının %10’u kadar silis dumanı ve silis dumanı, ve çimento ağırlık toplamının %2.00’si kadar da süperakışkanlaştırıcı (Gelenum 27) katkı kullanılmıştır. Tüm KYB’ların işlenebilirlik tayini için sırasıyla L-kutusu, V-tüneli, ve de akma tablası deneyleri yapılmıştır. Diğer taraftan; akışkanlık ve özgül ağırlık gibi bazı fiziksel özellik tayini, çekme, basınç ve eğilme dayanım, tokluk ve ayrıca 100 °C ve 200 °C sıcaklığa maruz kalmış numunelerde oluşmuş olan dayanıklılık testleri yapılmıştır. Sonuçlardan da belirtildiği gibi gibi, agrega yerine yerleştirilmiş olan atık PP parçalarının %25’ine kadar agrega yerine yerleştirildiği zaman, betonun KYB özelliğini kaybettiği görülmektedir. Diğer yandan, atık PP parçalarının KYB katılmasının işlenebilirlik değişikliğine ve de bazı dayanım kayıplara neden olduğu gözlemlenmiştir. Bunlar, çekme, basınç ve eğilme dayanımları; işlenebilirliğin azalması ve iç çatlakların oluşması durumları olarak verilebilir. Diğer taraftan, atık PP parçalarının KYB’da agrega yerine kullanılmasının; betonun sünekliğini ve tokluğunu arttırdığı, ağırlığının azaldığı yönlerinden betonda avantaj oluşturduğu anlaşılmıştır. Anahtar Kelimeler: Kendiliğinden yerleşen beton (KYB), Polypropylene atık plastik, Hafif agrega, Basınç dayanımı, Eğilme dayanımı, Çekme dayanımı, İşlenebilirlik, Tokluk, Isı dayanıklılığı.
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2018. Supervisor: Assist. Prof. Dr. Tülin Akçaoğlu.
Keywords: Civil Engineering; Aggregates (Building materials)--Concrete; Construction Engineering--Supplementary Cementitious Materials; Self Compacted Concrete; Polypropylene waste plastic; lightweight aggregate; compressive strength; splitting tensile strength; flexural strength; workability; flexural toughness; Heat degradation